The HEALERS: a patient, community, and stakeholder advisory board focus group series to refine a novel virtual world-based cardiac rehabilitation intervention and clinical trial - Abraham, Helayna; Anyetei-Anum, Grace Patrice; Krogman, Ashton; Clark, Donald; Echols, Melvin; Hall, Michael E.; Hodgman, Karen; Kaihoi, Brian; Kopecky, Stephen; Leth, Shawn; Malik, Shaista; Marsteller, Jill; et al. (Frontiers in Digital Health, 2025)
BackgroundCardiac rehabilitation (CR) is a widely underutilized secondary cardiovascular disease prevention strategy, due to a variety of barriers to participation that disproportionately impact women, minoritized racial and ethnic groups, and patients with low socioeconomic status. Destination Cardiac Rehab, a virtual world-based CR (VWCR) program designed by our team in collaboration with patients and community members to mitigate the barriers to CR participation, has demonstrated feasibility and acceptability. In anticipation of a randomized controlled trial (RCT) to further validate the intervention, this qualitative descriptive analysis provides insights garnered from a patient/community/stakeholder-advisory board (PCS-AB, HEALERS) focus group series, convened to inform iterative refinements to a RCT protocol.Methods and resultsHEALERS participated in five 90-min virtual focus group sessions to provide feedback on various aspects of the VWCR intervention and the recruitment/retention strategies. Major themes were identified from participant feedback to inform revisions to the trial protocol. Illustrative quotes were selected to represent each theme. Twenty-two members were recruited with diverse sociodemographic and personal/professional backgrounds (mean age 59.3 ± 13 years, 50% female). Regarding trial recruitment, members recommended effective communication strategies, recruitment video suggestions, and expansion of recruitment settings. HEALERS emphasized the importance of feeling safe during exercise and social support in designing an effective VWCR intervention. Lastly, they identified reminder messages, tangible incentives, and fostering positive relationships with the CR staff as important retention tools.ConclusionsA diverse PCS-AB was convened to better understand community needs to improve the patient-centric nature of Destination Cardiac Rehab in anticipation of an upcoming RCT. The HEALERS offered valuable insights that informed actionable changes to the RCT protocol.